Molecular Weights of Vesicular Stomatitis Virus and Its Defective Particles by Laser Light-Scattering Spectroscopy - Ware, B. R. (1973)
Laser light-scattering spectroscopy has been used to determine the diffusion coefficients of vesicular stomatitis virus and three of its defective particles in order to calculate their molecular weights.